Political Participation Convergence in Indonesia: A Study of Partisan Volunteers in the 2019 Election - Herdiansah, Ari Ganjar (UI Scholars Hub, 2019)
This paper offers an analysis of convergent political participation in Indonesia, which is represented by the strengthening role of partisan volunteers in elections. Using the library research method, this paper explains why partisan volunteers present strategic positions in elections, especially in 2019. The results of this research reveal that the strengthening of the positions of partisan volunteers in elections is driven by the level of public trust in weak political parties in a strict and complex multiparty system, the emergence of flexible and civic-style political participation, and the co-optation of the voluntary understanding and function by political parties to reach undecided voters. The existence of volunteers was initially based on the antithetical spirit of an elitist political process, but later became a complementary element for political parties in the effort to win elections. Consequently, the involvement of partisan volunteers can lead to transactional politics and signifies a shift in the meaning of volunteers to that of a pragmatic arena.